Factors Affecting Nurse Response Time in Indonesian Hospital Emergency Installation: A Literature Review - Nurul Imam; Taufan Citra Darmawan; Siska Christianingsih; Khalifatus Zuhriyah Alfianti (KHD-Production, 2024)
The success of handling cases in the Emergency Department is very dependent on the nurse's response time. However, nurses' response time is greatly influenced by many factors. The purpose of writing this systematic review is to find out in detail the Factors That Affect the Response Time of Emergency Department Nurses in Indonesian Hospitals. The study was identified systematically by searching the database through the keywords